OКУЛАРНИ МАНИФЕСТАЦИИ КАЈ ГОЛДЕНХАР СИНДРОМ- ПРИКАЗ НА СЛУЧАЈ - Бисера Велковска; Наташа Трпевска-Шекеринов; Емилија Ѓошевска-Даштевска; Маја Иванов (My University, 2020)
Goldenhar's syndrome (GS) is a complex syndrome characterized by a combination of abnormalities: hemifacial macrosomia, mandibular hypoplasia, ocular dermoids, ear abnormalities, and vertebral disorders. The incidence of GS is about 1 in 5000 to 25,000 live births. The male to female ratio is 3: 2.The etiology of this rare disease is not fully understood. The treatment protocol depends on the age of the patient and systemic clinical presentations. This paper presents a case of a 46-year-old woman with Goldenhar syndrome, which manifested with facial asymmetry, epibulbar dermoid, hearing loss, and scoliosis. Because it is a congenital syndrome, these people's lives are complex from an early age. There is a need for timely recognition of this syndrome and a multidisciplinary approach in treating these patients, with a team of specialist physicians, to enable them as much optimal functioning as possible in the environment. By presenting this case report, we would like to attract the attention of GS, which would be of educational significance for all physicians, primarily ophthalmologists, as well as otolaryngologists and orthopedists.
ОCULAR MANIFESTATION IN GOLDENHAR SYNDROME - CASE REPORT